Analisis Miskonsepsi Mahasiswa Pada Konsep Genetika Menggunakan Instrumen Four Tier Diagnostic Test - Sri Wulandari; Amelia Gusmalini*; Zulfarina Zulfarina (Jurnal Pendidikan Sains Indonesia, 2021)
Genetic has a broad and complicated topic and abstract material considered difficult by students. The inability to connect and construct between genetic concepts properly causes misconceptions. Therefore, the purpose of this study was to analyze students' misconceptions on the concept of genetics using a four-tier diagnostic test. 91 students from the Faculty of Education, Department of Biology, University of Riau were used as samples. The method was descriptive quantitative with a survey research model. The four-tier diagnostic test instrument consists of four levels: the first stage uses multiple-choice questions with four distractors questions and one key answer; the second level is the level of student confidence to choose the answers; the third level is the students' reasons for answering the questions; the fourth level is the level of student confidence to choose reasons. The number of questions tested was 20 questions with six sub-concepts. Confidence Discrimination Quotient (CDQ) and four-tier diagnostic test were used to analyze data on misconceptions and interpretation of student answer patterns. Students experienced misconceptions on 19 answer questions, 13 reason questions, and 16 answer and reason questions. The results of the four-tier diagnostic test described that the category of misconceptions was 65.21%, not understanding the concept was 24.53% and understanding the concept was 10.34%. From the six sub-concepts tested, the highest score of misconception was found in genetic material (75.1%) and the lowest was found in the scope of genetics (44.4%). On average, the students had medium and high categories of misconception